Hubungan Merokok Dengan Kejadian Hipertensi Pada Pria di Area Pedesaan Mojo Dowo Kecamatan Kemlagi Kabupaten Mojokerto. - Annisa Nurida; Yelvi Levani; M. Thoriq Hakam (Jurnal Keperawatan Muhammadiyah, 2019)
Objective:.This study aims to determine whether there is a relationship between smoking and the incidence of hypertension in men in rural areas.Methods: This study used observational analytic method with cross sectional approach. The population was participants who took part in social services in the village of Mojo Dowo, Kemlagi sub-district, Mojokerto district. The research sample was taken by total sampling after applying the inclusion and exclusion criteria to obtain 61 adult men.Results:Based on the outputs, the Asymp value is known. Sig (2-sided) in the Chi-Squere Pearson test is 0.967> 0.005, therefore it can be concluded that there is no relationship between smoking habits and the incidence of hypertension. Conclusion:From this study, it has been proven that there is no relationship between smoking habits and the incidence of hypertension in the villagers of Mojo Dowo. There may be other factors that cause hypertensionKeywords: smoking, hypertension, rural area